Pharmacogenetic considerations in the treatment of Alzheimer's disease. (June 2016) - Cacabelos, Ramón; Torrellas, Clara; Teijido, Oscar; Carril, Juan Carlos
The practical pharmacogenetics of Alzheimer's disease (AD) is circumscribed to acetylcholinesterase inhibitors (AChEIs) and memantine. However, pharmacogenetic procedures should be applied to novel strategies in AD therapeutics including: novel AChEIs and neurotransmitter regulators, anti-Aβ treatments, anti-tau treatments, pleiotropic products, epigenetic drugs and combination therapies. Genes involved in the pharmacogenetic network are under the influence of the epigenetic machinery which regulates gene expression transcriptionally and post-transcriptionally, configuring the fundamentals of pharmacoepigenomics. Over 60% of AD patients present concomitant pathologies demanding additional treatments which increase the likelihood of drug–drug interactions. Lipid metabolism dysfunction is a pathogenic mechanism inherent to AD neurodegeneration. The therapeutic response to hypolipidemic compounds is influenced by the APOE and CYP genotypes. The development of novel compounds and the use of combination/multifactorial treatments require the implantation of pharmacogenomic procedures for the avoidance of ADRs and the optimization of therapeutics.